2017 IEEE International Conference on Data Mining Workshops (ICDMW) 2017
DOI: 10.1109/icdmw.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Users’ Sentiment Towards Popular Consumer Industries and Brands on Twitter

Abstract: Abstract-Social media serves as a unified platform for users to express their thoughts on subjects ranging from their daily lives to their opinion on consumer brands and products. These users wield an enormous influence in shaping the opinions of other consumers and influence brand perception, brand loyalty and brand advocacy. In this paper, we analyze the opinion of 19M Twitter users towards 62 popular industries, encompassing 12,898 enterprise and consumer brands, as well as associated subject matter topics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 13 publications
0
24
0
3
Order By: Relevance
“…When the airline industry analysis is broken down further, it is seen that the consumers are extremely negative towards Spirit, Delta, and United, whereas they are pretty positive towards Air-Mauritius, Sun-Country and Thomas Cook. This information is essentially crucial for these companies to know where they can reduce the service gap [6].…”
Section: A Applications In Businessmentioning
confidence: 99%
“…When the airline industry analysis is broken down further, it is seen that the consumers are extremely negative towards Spirit, Delta, and United, whereas they are pretty positive towards Air-Mauritius, Sun-Country and Thomas Cook. This information is essentially crucial for these companies to know where they can reduce the service gap [6].…”
Section: A Applications In Businessmentioning
confidence: 99%
“…There are images, links, emoticons and other forms of media included. Hence, the first step of our analysis is to clean the tweets we have collected [28]. Tokenization is also difficult due to the body of the text.…”
Section: A Sentiment Information Visualisationmentioning
confidence: 99%
“…Tokenization is also difficult due to the body of the text. We would need to make sure that the @-mentions, emoticons, links and #hash-tags are preserved as individual tokens and not ignored, since these are equally important aspects of the analysis [27], [28]. In this research we follow the method as shown in Fig.…”
Section: A Sentiment Information Visualisationmentioning
confidence: 99%
“…Sentiment analysis is described as the fi eld of study that analyzes people's opinions, sentiments, evaluations, appraisals, attitudes, and emotions towards entities, such as products, services, organizations, individuals, issues, events, topics, and their attributes (Liu, 2012). In fact, rather than answering surveys about products and services, consumers freely express their thoughts and emotions on social media (Hu et al, 2017). Sentiment analysis tasks can be done at several levels, as suggested by Kumar and Sebastian (2012): word level, phrase or sentence level, document level, and feature level.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Indeed, sentiment monitoring might enable companies to improve product quality and services, assess the impact of promotional campaigns, drive sales, and identify new business opportunities. Another highly relevant outcome of measuring sentiment is gauging users' perceptions of companies (Hu et al, 2017;Jansen, Zhang, Sobel & Chowdury, 2009). Given their pressing environmental and sustainability-related concerns, companies have been carefully developing their identities as "green brands".…”
Section: Introductionmentioning
confidence: 99%